Effect of dose and combination of antihypertensives on interindividual blood pressure variability: a systematic review. - Webb, A; Rothwell, P (2011)
BACKGROUND AND PURPOSE: Recent studies have shown that visit-to-visit blood pressure variability is a powerful risk factor for stroke, is reduced by calcium channel blockers and diuretics, and increased by β-blockers. However, it is unknown whether these effects are dose-dependent and persist in combination with other drugs. METHODS: Cochrane and Medline databases were searched for systematic reviews and randomized controlled trials of antihypertensive drugs. Eligible trials randomized all patients to a combination of drug classes or different doses of the same drug. Baseline and follow-up data for mean (SD) systolic blood pressure (SBP) and diastolic blood pressure were extracted. Differences in interindividual variance (SD2) in blood pressure were expressed as a ratio (VR). Estimates were pooled by random-effects meta-analysis. RESULTS: Calcium channel blockers reduced interindividual variability in SBP when added to another agent (VR, 0.75; 95% CI, 0.64 to 0.87; P=0.0002; 12 trials; 1565 patients) with a smaller reduction with diuretics (VR, 0.85; 0.71 to 1.01; P=0.07; 17 trials; 3217 patients). Adding other agents to calcium channel blockers did not significantly affect SBP variability (VR, 1.06; 0.83 to 1.34; P=0.65; 12 trials; 1460 patients) despite a 5.8-mm Hg reduction in mean SBP. Randomization to a higher dose of calcium channel blockers reduced SBP variability (VR, 0.84; 0.74 to 0.94; P=0.004; 25 trials; 2179 patients), whereas randomization to a higher dose of β-blockers increased SBP variability (VR, 1.31; 1.01 to 1.69; P=0.034; 6 trials; 486 patients). CONCLUSIONS: Effects of antihypertensive drugs on SBP variability are dose-dependent and persist when used in combinations. Use of a high dose of a calcium channel blocker alone or in combination with other agents is therefore likely to be particularly effective in prevention of stroke.